Obesity screening for young Japanese males and females using skin fold measurements: the classification revisited - Kagawa, M.; Uenishi, K.; Mori, M.; Uchida, H.; Kerr, Deborah; Binns, Colin; Hills, A. (H E C Press, 2010)
Anthropometric assessment is a simple, safe, and cost-efficient method to examine the health status of individuals. The Japanese obesity classification based on the sum of two skin folds (S2SF) was proposed nearly 40 years ago therefore its applicability to Japanese living today is unknown. The current study aimed to determine S2SF cut-off values that correspond to percent body fat (%BF) and BMI values using two datasets from young Japanese adults (233 males and 139 females). Using regression analysis, S2SF and height-corrected S2SF (HtS2SF) values that correspond to %BF of 20, 25, and 30% for males and 30, 35, and 40% for females were determined. In addition, cut-off values of both S2SF and HtS2SF that correspond to BMI values of 23 kg/m2, 25 kg/m2 and 30 kg/m2 were determined. In comparison with the original S2SF values, the proposed values are smaller by about 10 mm at maximum. The proposed values show an improvement in sensitivity from about 25% to above90% to identify individuals with =20% body fat in males and =30% body fat in females with high specificity of about 95% in both genders. The results indicate that the original S2SF cut-off values to screen obese individuals cannot be applied to young Japanese adults living today and modification is required. Application of the proposed values may assist screening in the clinical setting.